Blast-related mild traumatic brain injury in the acute phase: Acute stress reactions partially mediate the relationship between loss of consciousness and symptoms. (July 2014) - Norris, Jacob N.; Sams, Richard; Lundblad, Peter; Frantz, Earl; Harris, Erica
Abstract Primary objective: The objective was to compare symptoms in service members diagnosed with a blast-related mTBI (mild traumatic brain injury) with a loss of consciousness (LOC) to those without LOC. Research design: Clinicians saw US military personnel within 72 hours of sustaining a blast-related mTBI and at a follow-up visit 48–72 hours later (n = 210). Methods and procedures: Demographics, post-concussive symptoms, diagnosis of acute stress reaction (ASR) and simple reaction time data from the Automated Neuropsychological Assessment Metric (ANAM) were collected. Main outcomes and results: ASRs were significantly more likely in patients reporting LOC versus patients reporting no LOC. At the first post-injury visit, LOC was associated with difficulty sleeping, hearing loss, memory problems and reporting more symptoms. A follow-up analysis explored if symptomatic differences were influenced by ASR. Adjusting for ASR, the statistical relationships between LOC and symptoms were weaker (i.e. reduced Odds Ratios). At the follow-up visit, difficulty sleeping was associated with LOC before and after adjusting for ASR. Patients with both ASR and LOC had the slowest simple reaction times. Conclusions: Results suggest ASR may partially mediate symptom presentation and cognitive dysfunction in the acute phase following blast-related mTBI. Future research is warranted.